Histological chorioamnionitis and its predictors among mothers with premature rupture of membranes delivering at tertiary hospitals in Uganda: a multicenter cross-sectional study - Ibrahim Abdi Abdinasir; Marie Pascaline Sabine Ishimwe; Maxwell Okello; Paul Byaruhanga; Ralph Samson Enyamitoit; Theoneste Hakizimana (BMC Pregnancy and Childbirth)
Abstract Background Histological chorioamnionitis (HCA) is a significant global threat to maternal and fetal health, with an increasing prevalence in resource-limited settings. However, data on its burden and predictors remain scarce in Africa, including Uganda. This study aimed to determine the prevalence and predictors of HCA among mothers with premature rupture of membranes (PROM) at three tertiary hospitals in Uganda. Methods This multicenter cross-sectional study was conducted over a three-month period, from July to October 2023, at three tertiary hospitals in Uganda. A total of 106 women diagnosed with PROM were consecutively enrolled. Data were collected using a structured questionnaire that captured routine history-taking and physical examinations. Key information gathered included the history of liquor drainage, clinical signs of chorioamnionitis (fever, uterine tenderness, and foul-smelling liquor), labor history, and placental samples obtained after delivery for histopathological analysis. Descriptive statistics and binary logistic regression analyses were performed using STATA version 14.2. Statistical significance was set at P < 0.05, with a 95% confidence interval. Results were presented using bar charts, pie charts, and tables. Results Among the 106 participants with PROM, 44 (41.5%) had histological chorioamnionitis. The most common histological finding was neutrophil infiltration in 22 cases (50.0%), followed by funisitis in 13 cases (29.6%). Referral status (aOR = 4.5, 95% CI: 1.511–13.315, p = 0.007) and lack of prenatal care (PNC) attendance (aOR = 9.8, 95% CI: 2.802–14.504, p = 0.000) were independently associated with histological chorioamnionitis. Conclusions and recommendations. The prevalence of HCA in this study was notably higher than previously reported data from Uganda. Neutrophil infiltration was the most frequently observed histological lesion. Patients with PROM who were referred from other health facilities or had not attended PNC were at a higher risk of developing HCA. These findings highlight the critical need for early detection and management of HCA in mothers with PROM, particularly in resource-limited settings. Routine screening for HCA should be implemented for all women presenting with PROM, with special attention to referred cases and those without PNC. Early initiation of treatment should be considered until the diagnosis is definitively ruled out. Further research is needed to explore the underlying causes of HCA to inform targeted preventive measures.